CIPROFLOXACIN RESISTANCE AMONG CLINICAL ISOLATES FROM ACUTE RESPIRATORY INFECTIONS (ARIs) PATIENTS AT COMMUNITY HEALTH CENTERS IN TASIKMALAYA, INDONESIA - Ramdhani, Danni; Kusuma, Sri Agung Fitri; Mustarichie, Resmi; Febriana, Elin; Sediana, Dede; Afifi, Mokhamad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Acute respiratory infections (ARIs) are acute infections of any part of the respiratory tract and related structures including middle ear, paranasal sinuses, and pleural cavity. This study was to determine the resistance in isolates of the pathogen of the patients with acute respiratory infections in clinics in Tasikmalaya against antibiotic ciprofloxacin and effectiveness of this antibiotic. Methods: Isolates were obtained fromswabs cavity of 332 patients with acute respiratory infections. Ciprofloxacin resistance against pathogenic isolates of diseased patients ARIs was determined by using paper disk diffusion method. Results:The patient isolates shows that it is resistance to the antibiotic ciprofloxacin with the percentage of 19.81%. Conclusion:Ciprofloxacin level of antibiotic resistance being mediated resistance. Routine surveillance and education to health professionals and patients is very important to overcome the problem. Â 